2022
DOI: 10.1088/1755-1315/961/1/012071
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Performance of Energy Dissipation Slotted Plate for Bridge Unseating Prevention

Abstract: Recently, the bridge unseating prevention devices are widely used in active seismic zones. These devices are stiffness dependant, velocity dependant and energy dissipation devices. The energy dissipation devices are designed to overcome the energy that transfers from bridge substructure to superstructure. However, the current devices are not controlled to function with different ground motion intensities and should be replaced after yielding. Therefore, this research introduced a slotted plate energy dissipati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Numerical simulations and experimental testing have widely been performed on restrainers, dampers and bridges equipped with these devices [8][9][10]. The results revealed that utilizing the bridge with supplementary damping system is resulting to improve the bridges performance during seismic excitation [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Numerical simulations and experimental testing have widely been performed on restrainers, dampers and bridges equipped with these devices [8][9][10]. The results revealed that utilizing the bridge with supplementary damping system is resulting to improve the bridges performance during seismic excitation [11][12][13].…”
Section: Introductionmentioning
confidence: 99%